Integrated comparative transcriptome and physiological analysis reveals the metabolic responses underlying genotype variations in NH4+ tolerance - Chen, Haifei; Lv, Wei; Zhang, Wenqi; Zhao, Jie; Zhang, Quan; Zhang, Zhenhua (Frontiers in Plant Science, 2023)
Several mechanisms have been proposed to explain NH4 + toxicity. However, the core information about the biochemical regulation of plants in response to NH4 + toxicity is still lacking. In this study, the tissue NH4 + concentration is an important factor contributing to variations in plant growth even under nitrate nutrition and NH4 + tolerance under ammonium nutrition. Furthermore, NH4 + led to the reprogramming of the transcriptional profile, as genes related to trehalose-6-phosphate and zeatin biosynthesis were downregulated, whereas genes related to nitrogen metabolism, camalexin, stilbenoid and phenylpropanoid biosynthesis were upregulated. Further analysis revealed that a large number of genes, which enriched in phenylpropanoid and stilbenoid biosynthesis, were uniquely upregulated in the NH4 + -tolerant ecotype Or-1. These results suggested that the NH4 + -tolerant ecotype showed a more intense response to NH4 + by activating defense processes and pathways. Importantly, the tolerant ecotype had a higher 15 NH4 + uptake and nitrogen utilization efficiency, but lower NH4 + , indicating the tolerant ecotype maintained a low NH4 + level, mainly by promoting NH4 + assimilation rather than inhibiting NH4 + uptake. The carbon and nitrogen metabolism analysis revealed that the tolerant ecotype had a stronger carbon skeleton production capacity with higher levels of hexokinase, pyruvate kinase, and glutamate dehydrogenase activity to assimilate free NH4 + , Taken together, the results revealed the core mechanisms utilized by plants in response to NH4 + , which are consequently of ecological and agricultural importance.